how to solve: (15x^-1y^2 / 5xy^-4) ^-1


Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

how to solve: (15x^-1y^2 / 5xy^-4) ^-1

i have no clue on how to work this problem

Research, Knowledge and Information :



Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

15x^2y^2-5xy^2-150y^2= - Get Easy Solution


Simple and best practice solution for 15x^2y^2-5xy^2 ... -5xy 2 + 15x 2 y 2 + -150y 2 = 0 Solving -5xy 2 ... Add '-1y 2 ' to each side of the equation. y 2 + -1y 2 ...
Read More At : www.geteasysolution.com...

15x^2y^2-5xy^2-150y^2=0 - Get Easy Solution


Simple and best practice solution for 15x^2y^2-5xy^2 ... -5xy 2 + 15x 2 y 2 + -150y 2 = 0 Solving -5xy 2 ... Add '-1y 2 ' to each side of the equation. y 2 + -1y 2 ...
Read More At : www.geteasysolution.com...

how to factor y^2+2xy-15x^2? - Weknowtheanswer


how to factor y^2+2xy-15x^2? Answer for ... 15x^2 => y^2 + (5xy - 3xy) - 15x^2 => y*(y + 5x) - 3x ... 150x 2 y 2 = 0 Solving 10 + -20xy + -150x 2 y 2 = 0 Solving for ...
Read More At : www.weknowtheanswer.com...

Can I Have Assistance With Three Problems? 1. (3x^... | Chegg.com


(3x^2y-4) (4x^-3y) 2. (15x^-1y^2/5xy^-4)-1 3. 24x^-1y^-2/6x^-4y^3 ... 1. (3x^2y-4) (4x^-3y) 2. (15x^-1y^2/5xy^-4)-1. 3. 24x^-1y^-2/6x^-4y^3. Best answer. 100 % (1 ...
Read More At : www.chegg.com...

SOLUTIONS TO IMPLICIT DIFFERENTIATION PROBLEMS


SOLUTIONS TO IMPLICIT DIFFERENTIATION PROBLEMS ... + 2 y' + 3x 2 + 4x, so that (Now solve for y' .) 1 ... 1 - y - 3x 2 - 4x = (3y 2 + x + 2) y' ,
Read More At : www.math.ucdavis.edu...

What is the simplified form of (-3x^3y^2)(5xy-1) a.) 15^2/y^2 ...


What is the simplified form of (-3x^3y^2)(5xy-1) - 1621925. 1. ... (-3)(5)} {(x^3 * x)} {(y^2 * y^-1} {-15} { x^3+1} { y^2-1} {-15} {x^4} ... Solve for x. 3.3x = 29.04
Read More At : brainly.com...

Simple Polynomial Factoring (page 2 of 3) - Purplemath | Home


Simple Polynomial Factoring (page 2 of 3) Sections: Simple factoring, Factoring "in pairs" Factor x 2 y 3 + xy; I ... 3x 3 + 6x 2 – 15x = 3x( ) = 3x(x 2 ...
Read More At : www.purplemath.com...

How do you implicitly differentiate xy + 3x + 5x^2 = 4 ...


... = 1y + xdy/dx = y + xdy/dx When y is differentiated WRT x in implicit ... How do you implicitly differentiate # xy + 3x + 5x^2 = 4#? ... How to solve this?
Read More At : socratic.org...

How do you multiply 3xy(-x^4-4x^2 y+5xy^2) ? | Socratic


... (blue)(-3x^5y - 12x^3.y^2 + 15x^2y^3 color(blue)(3xy)(-x^4-4x^2y+5xy^2) =color(blue ... How do you multiply #3xy(-x^4-4x^2 y+5xy^2) #? ... How do solve #3/(x+1) ...
Read More At : socratic.org...

Math 432 HW 2.5 Solutions


(2xnym+2 – 6xn+1ym+1) dx + (3xn+1ym+1 – 4xn+2ym) dy = 0 ... (3n – 1) – 2n = 1, and solving. . . 3(3n – 1) – 4n = 2 9n – 3 – 4n = 2 5n = 5 n = 1 m = (3 ...
Read More At : faculty.frostburg.edu...

Suggested Questions And Answer :



Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how to solve: (15x^-1y^2 / 5xy^-4) ^-1


Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

((x)/(5y)-(1)/(4))/((3)/(4y)-(2)/(x))

 x            1 ----  -    ------- 5y           4 -----------------  3         2 ---   -&n
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve y= 5x+2, x=6-3y. this is systems of equations :)

Problem: solve y= 5x+2, x=6-3y. this is systems of equations :) please help me l0l 1) y = 5x + 2 2) x = 6 - 3y Substitute the value of y, from equation 1, into equation 2. x = 6 - 3y x = 6 - 3(5x + 2) x = 6 - 15x - 6 x + 15x = 6 - 15x - 6 + 15x 16x = 6 - 6 16x = 0 x = 0 Use that
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

-3+2(9x-5)=5(3x+2)

Problem: -3+2(9x-5)=5(3x+2) how do you solve this algebra equation? -3 + 2(9x - 5) = 5(3x + 2) -3 + 18x - 10 = 15x + 10 18x - 13 = 15x + 10 18x - 13 + 13 = 15x + 10 + 13 18x = 15x + 23 18x - 15x = 15x + 23 - 15x 3x = 23 3x/3 = 23/3 x = 23/3 Check it. -3 + 2(9x - 5) = 5(3x + 2) -3
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

How to solve for the centroid of A(4,2), B(12,6) and C(7,13)

The three points make up a triangle. We need to find the central points of each side. This helps us to establish the medians from each corner of the triangle to the midpoint of the opposite side. The centroid will be located where the medians intersect. The sides of the triangle are AB with midpoint
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

3x(5x-7) -2(8x+3)

Problem: 3x(5x-7) -2(8x+3) How do i solve this problem Step by step, as always. 3x(5x - 7) - 2(8x + 3) (15x^2 - 21x) - 2(8x + 3) (15x^2 - 21x) - (16x + 6) (15x^2 - 21x) - (16x + 6) 15x^2 - 21x - 16x - 6 15x^2 - 37x - 6  
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve following system of equations

Problem: solve following system of equations solve the following system of equations: x-2y+z=6 , 2x+y-3z=-3, x-3y+3z=10 1) x - 2y + z = 6 2) 2x + y - 3z = -3 3) x - 3y + 3z = 10 Multiply equation 1 by 3. 3(x - 2y + z) = 6 * 3 4) 3x - 6y + 3z = 18 Add equation 2 to equation 4. &nbs
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve for x and y: 15x- 18- 2y= -3y+ y, 10x+ 7y+ 20= 4x+ 2

solve for x and y: 15x- 18- 2y= -3y+ y, 10x+ 7y+ 20= 4x+ 2 We'll work both equations to get the x and y terms on the left, and any constant value on the right. 15x - 18 - 2y= -3y + y 15x - 2y + 3y - y = 18 15x = 18 x = 18/15 x = 6/5 Now, we'll begin solving the second equation, and substitute the
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve 15x+24=8(10+3x)-2

solve 15x+24=8(10+3x)-2 15x + 24 = 8(10+3x) - 2 15x + 24 = 80 + 24x - 2 15x - 24x = 80 - 2 - 24 -9x = 54 x = -6
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve for x : 15x + 34 = 3x - 9

15x + 34 = 3x - 9 15x - 3x = -9 - 34 12x = -43 x = -43 / 12
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.0869 seconds